Representing the Invisible. The Integral Plan for the Architectural and Cultural Landscape of Maní, Yucatán - Laura María Lázaro San José (Diségno)
For a place to be identified as a landscape, there is first a personal decision to differentiate it as an element of value; then there is a necessary process of transversal argumentation of its landscape intensity, and finally, it is disseminated in a clear and accessible way. However, on many occasions, what is really necessary is a method of visibility, of representation of blurred or unnoticed landscapes, which does not consist so much in contemplating the physical environment, but in understanding the cultural and collective memory that they hold. In this direction, the case of the Integral Plan for the enhancement of the landscape of Maní in Yucatán (Mexico) is presented as an example in which its graphic interpretation is a key tool for rescuing and conserving its cultural heritage. The ancient colonial city, and former Mayan ceremonial center, has come down to us today as a confused space of overlapping and unintelligible memories. The Plan –elaborated at intercontinental distance, without previous graphic documentation and affected by the restrictions of the COVID-19 pandemic– proposes to define the city from a personal vision and by means of different systems of representation and scales to offer a synthetic and comprehensible reading of the whole. Therefore, in this case, the choice of an eloquent method of graphic interpretation of the architecture, landscape and territory becomes the most effective instrument for the dissemination of heritage that is now culturally accessible.